Exploring motivation and improving English speaking proficiency: A literature study on role-play method - Rohmiyati, Yuli; Asiah, Nur (Institute of Computer Science (IOCS), 2024)
Motivation is a crucial role in language learning as it influences students' willingness, effort, and engagement in the learning process. When students are motivated, they are more likely to actively participate, persist through challenges, and ultimately achieve higher levels of language proficiency. Role-play methods offer a dynamic approach that can effectively address the motivation challenges faced by teachers. By immersing students in simulated real-life scenarios, role-play creates an interactive and engaging learning environment. The study intends to explore motivation and improve English speaking proficiency using role-play method. This study use qualitative with literature study. The research found that role-play activities are able to increase students' engagement, real-world language application, speaking skills, confidence, creativity, and collaborative learning, ultimately leading to enhanced motivation in learning English speaking.